Dampak Globalisasi Terhadap Pasar Tradisonal Di Indonesia - Cicik Khildar Rizqi; Dety Mulyanti (Manajemen Kreatif Jurnal, 2023)
Globalization is an unavoidable phenomenon involving various sectors, when all of countries in the world has been integrated become one market that is that is no limited by territorial area. In the economy and trade, Globalization has affected various social structures. The large number of foreign investor has entered to Indonesia is one of the effects of globalization in the world of economy and trade. Investation is one of the key for strengthening process in economic development. The business sectors has become a destination for investation is a modern retail industry. There is investation with capital strength in the modern retail industry sector make modern markets has begin, such as Supermarkets and Hypermarkets, Mini Markets and Mall. The investation in the modern market are mushrooming and uncontrollable, it makes competition between modern markets, especially supermarket in Indonesia. Foreign investor has big capital also take part for this investation. Ease come an investor as a result of the globalization era is a challenge for the economic development of the common people, in this case micro, small and medium enterprises in traditional markets. The progress of modern market are rapidly and unstoppable, if it is allowed to continue, traditional markets which are forum for middle and lower economic actors, one of which is small traders, street vendors, etc. will be sidelined and displaced.